TIGA RUNGGU VILLAGE SIAM ORANGE FARMING BUSINESS DEVELOPMENT STRATEGY REVIEWED FROM AN ISLAMIC PERSPECTIVE - Siregar, Gustina; Putra, Yudha Andriansyah; Sabri, Tio Ardhito (Proceeding International Seminar of Islamic Studies, 2024)
Simalungum Regency, Tigga Runggu District is one of the areas that has the potential for economic excellence in the form of natural resource wealth to be developed, namely the horticultural agricultural sector which has an important role in supplying adequate nutrition for the community, especially oranges with high vitamin C content, but this high potential is not supported by easy access to increase farmers' production and income with strategic planning from an Islamic perspective. This research is quantitative. Researchers will describe the situation in the field to find a strategy formulation for developing the contribution of horticultural  farming  businesses  using  SWOT analysis.  From  the  results  of  the  Internal Factors Analysis Summary (IFAS) and External Factors Analysis Summary (EFAS) quadrant analysis, it is clear that "the contribution of Siamese orange farming businesses in Tigga Runggu sub-district has low competitive power to face threats from other agropolitan areas. Therefore, the strategy focuses on agricultural mechanisms and optimization as well as target markets.  The  steps that  need  to  be  taken  include  improving  infrastructure  facilities and infrastructure (Assembly), providing guidance and counseling to farmers, and collaborating with partners between the government, the private sector, and farmers or stakeholders to carry out related on-farm and off-farm activities. with post-harvest management where the production results will be brought in raw or processed form. This research aims to identify the key  internal  and  external  factors  that  influence  Siamese  orange  farming.  The  research location was determined purposively with the consideration that the area is the center of orange production in Simalungun Regency. The results of the research that has been carried out show alternative strategies for developing Siamese orange farming, namely: (a) S-O (Strengths-Opportunities) Strategy: Increasing the land area will increase the demand for orange fruit. (b) W-O (Weakness-Opportunities) Strategy: The higher demand for citrus fruit will  increase  farmers'  capital.  (c)  S-T (Strengths-Threats)  Strategy:  Maximizing  farming experience to reduce pest and disease attacks, improving product quality to face similar business competition. (d) W-T (Weakness-Threats) Strategy: Pay attention to production by implementing appropriate integrated pest management (IPM) and improving care for Siam orange plants.